Scoparone attenuates cholestatic liver injury through regulating hepatic bile acid metabolism, ameliorating periductal fibrosis and inhibiting inflammatory response - Juan Hao; Xiaoyu Shen; Kan Lu; Yi Xu; Yiyue Chen; Jibo Liu; Xiaohong Shao; Chunling Zhu; Yaqin Ding; Xin Xie; Jian Wu; Quanjun Yang (Pharmacological Research - Modern Chinese Medicine, 2023)
Background: Cholestatic liver disease (CLD) encompasses a broad spectrum of etiologically heterogeneous hepatobiliary disorders with common features, including ductal reaction, periductal fibrosis, and inflammatory response. Scoparone (SCO) is a bioactive component of the herbal medicine Artemisia capillaris Thunb that is used clinically for the treatment of hepatic dysfunction, cholestasis and jaundice. Aim: To investigate the therapeutic effect of SCO against 3,5-diethoxycarbonyl- 1,4- dihydrocollidine (DDC) induced CLD. Materials and methods: In the present study, two independent experiments were conducted to comprehensively analyze the hepatoprotective and hepatotoxicity effects of SCO against DDC diet-induced CLD. First, three doses of SCO (5, 15, and 45 mg/kg) were injected intraperitoneal daily for 14 days in DDC diet-induced CLD for the pharmacological research. Then, a high dose of SCO (45 mg/kg) was used for 28 days in negative and CLD model mice to evaluate the therapeutic potential of SCO. Results: DDC-induced CLD mice exhibited hepatomegaly and weight loss with hepatic pathological features including hepatocyte and bile duct damage, bile acid metabolism abnormalities, peribiliary fibrosis, and inflammatory factor infiltration. Treatment with three doses of SCO (5, 15 and 45 mg/kg) produced dose-dependent hepatoprotective effects, attenuated fine bile duct responses, ameliorated peribiliary fibrosis and suppressed intrahepatic inflammatory responses. SCO inhibited the expression of Cyp2b10, a bile acid phase I metabolizing enzyme, and Sult2a1, a phase II metabolizing enzyme, in DDC diet-induced CLD mice. Meanwhile, SCO inhibited the expression of Tgfb1, aSMA, Timp1 and Col1a1. SCO suppressed liver inflammation by reducing the infiltration of myeloid cells and lymphocytes. SCO suppressed DDC-induced lymphocyte infiltration. In addition, normal control mice treated with SCO showed no significant changes in liver injury, bile duct reaction, peribiliary fibrosis and inflammatory infiltration. Conclusion: SCO exerts a pharmacological effect on the reprogramming of hepatic bile acid metabolism, hepatic fibrosis and inflammatory response, thus having potential for the treatment of CLD.